BMBE Law Public Information Campaign (BLPIC): A Strategic Communication Intervention Plan to Foster BMBE Law Awareness - Manipol, Vergel S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The study proposes a Strategic Communication Plan "an Interven-tion Plan" designed to enhance the implementation of the Barangay Mi-cro Business Enterprises (BMBE) Law. The intervention plan addresses the current gaps in awareness and utilization of the law's incentives, particularly focusing on three key areas: 1) Technology Transfer, Pro-duction and Management Training, and Marketing Assistance; 2) Trade Investment and Promotions; and 3) Special Credit Delivery, which has been identified as the least availed incentive. The study utilized descrip-tive-secondary data analysis "non-experimental" and focused on syn-thesizing findings and recommendations from previous related studies to create a comprehensive and actionable communication plan. The proposed BMBE Law Public Information Campaign (BLPIC) integrated targeted activities, including seminars, conferences, and symposiums, to foster wider and more effective dissemination of information. These activities aim to mitigate the low to moderate implementation levels of the law, particularly in rural and remote areas, by emphasizing the ben-efits and accessibility of the incentives.The plan recommended a multi-stakeholder approach, engaging lo-cal government units, financial institutions, and business development organizations to ensure a cohesive and far-reaching campaign. By prior-itizing the Special Credit Delivery incentive, the plan seeks to address its underutilization while simultaneously enhancing awareness of the other incentives. The intervention also underscores the importance of leveraging digital platforms and community-based outreach to maxim-ize reach and engagement. Ultimately, the BLPIC aims to make the BMBE Law more meaningful, relevant, and accessible, thereby fostering economic growth and sustainability for micro-enterprises across di-verse communities.